La injuria en imágenes: el vilipendiado honor de los hombres públicos chilenos en la prensa satírica (1860-1900) - Tomás Cornejo Cancino (Nuevo mundo - Mundos Nuevos, 2006)
Using various discursive strategies, cartoons violated the respectable public image that chilean upper class had built of it self. The attack to most recognized dignitaries’ social esteem, show them in their intimacy, devoid of their elegant suits, full of vices and lacking of all virtue. This essay analyzes two increasing moments of insulting attacks made through cartoons: the first, in 1868, against politician, writer and historian Benjamín Vicuña Mackenna; the second, in the 1880-1890s, watching the effects of Juan Rafael Allende’s satirical periodicals against the whole elite. So, relationships between public and private honor get discovered.